Analisis Tingkat Kepuasan Pelanggan Aplikasi Jamride Penajam Paser Utara Menggunakan Metode PIECES - Afrina Afrina; Joy Nashar Utamajaya; Surmiati Surmiati (STMIK Budi Darma, 2022)
Jamride PPU is an online motorcycle taxi service application and food delivery that operates in North Penajam Paser Regency and Paser Regency which is managed by CV. Jamride Multimedia and officially obtained a business license on October 21, 2019. Jamride seeks to provide services to the community by providing services that meet their daily needs. Jamride has several main services that are not inferior to similar applications using their services, such as motorbike pick-up services, car services, food delivery services, shopping services to the market, and shopping at specific stores. determine the attitude that is determined based on the experience gained. goal is an assessment of the quality or characteristics of a product, service, or product itself that provides consumer satisfaction in terms of meeting consumer needs. customers are created through service quality and value. This survey aims to analyze customer satisfaction with Jamride PPU Online Transport. This study uses quantitative descriptive data, Likert scale, performance, information, economy, control and service, efficiency, and service. As a system analysis tool, PIECES pays special attention to detailed and comprehensive systems, identifies system strengths and weaknesses, and uses them as a reference for further enterprise development. Jamride PPU has reached a value of 4.01. This means that customer satisfaction with existing services is included in the PUAS category